QR Based Student Attendance Management App: A Case Study of Kabale University. - Nuwasasira, Chranimah (Kabale University, 2024)
The importance of the QR-based student attendance management System is steadily increasing due to the evolution of new technologies and high-capacity storage media but also because of growing studies at Institutions to reduce the dodging of students.